INOVASI PEMBELAJARAN PLH DALAM SAINS UNTUK MEMBANGUN KARAKTER BERWAWASAN LINGKUNGAN SISWA BERBASIS MOTORIC - Sukarjita, I Wayan (STKIP Santu Paulus Ruteng, 2018)
done the theoretical study to find the weaknesses of learning for Environmental Education (PLH) were implemented in the schools by the integrative technic and their alternative solutions. Based on the theoretical study, the learning process of PLH in the schools has been more particularly informative (emphasis of cognitive aspect). Supposedly, PLH learning in the schools more emphasis on the development of attitudes and behavior (character) by the contextually. One of the learning that combines character education, contextual learning and usefully media is MOTORIC learning model that is an innovation of PLH learning in the schools with a series of phases of learning are: Motivation, Observation, Talking, Orientation, Reflection, Implementation and Confirmation. Through the application of MOTORIC learning models for PLH on on the schools, is expected to grow the environmental attitudes and behavior for the students.